Pengaruh Reputasi Auditor, Karakteristik Perusahaan dan Disclosure Terhadap Opini Audit Going Concern - Miswaty; Fristantia Widarta Wong; Yanzil Azizil Yudaruddin (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2022)
The purpose of this reseach was to determine the effect of results Auditor's Reputation, Company’s Growth, Company’s Financial Condition, Company’s Size, and Disclosure both simultaneously and partially on Opinion of auditor about how the firm can sustain. The data used are existing sources, both internal and external, and data can be accessed via the internet and information publication. The data used are the financial statements of Financial of firm that published in Indonesian capital market 2018-2019. Multivariate analysis is employed to test hypothesis. This results shows that disclosure affect going concern audito opinion negatively and significantly. While auditor’s reputation, Company’s Growth, Company’s Financial Condition and Company’s Size have no effect on going concern audit opinion.